The language of literature : linguistic approaches to classical texts - Allan, Rutger J.; Buijs, Michel. (Amsterdam studies in classical philology, 2007)
This volume is a collection of papers revealing the largely unexplored boundary between linguistic and literary approaches to classical texts. Eleven contributions by various scholars discuss a wide range of linguistic and literary apects of classical texts: the narratee in the prologues of Sophocles' Trachiniae and of Euripides, the chronology in Pindar's Odes, the relation between tense-aspect and Discourse Modes in Thucydides, Xenophon, Vergil and Ovid, the use of aspect in the Law Code of Gortyn, expressions of futurity and the word order of adjectives in Herodotus, and, finally, ancient and modern views on word order. Following an interdisciplinary approach, all contributions aim at bridging the gap between linguistic and literary study of classical texts.